P20 A comparison of the cardiovascular effects of empagliflozin and liraglutide: a systematic review and meta-analysis. (26th October 2016) - Mordi, I; Kang, J; Mordi, N; Singh, J; McCrimmon, R; Leese, G; Struthers, A; Lang, CC
Abstract : Background: With the recent publication of the EMPA-REG Outcome and LEADER trials, we now have two diabetes drugs which improve cardiovascular outcome. The aim of this study was to conduct a meta-analysis of the CV effects of empagliflozin and liraglutide to provide a better understanding of the mechanisms that may have led to these positive results. Methods: A systematic search was carried out. RCT of empagliflozin and liraglutide against both placebo and active comparator were included. In total 52 studies were included, involving 33, 500 patients in total (empagliflozin: 14, 415 patients; liraglutide: 19, 085 patients). Various CV parameters were compared. Meta-analysis was conducted using REVMAN 5.3. Results: Both empagliflozin and liraglutide caused a significant reduction in weight and systolic blood pressure. Empagliflozin also caused a significant drop in BP. There was a significant increase in heart rate with liraglutide. Liraglutide caused a significant decrease in lipid parameters whereas empagliflozin caused a significant increase in lipids. Conclusions: The results of this meta-analysis might provide some explanation for the cardiovascular effects seen in LEADER and EMPA-REG. Empagliflozin's reduction in weight and BP may partially explain its beneficial effects on heart failure, while the increase in cholesterol may also explain why there was no significant difference in MI and a trend to increased stroke risk. The reduction in cholesterol and blood pressure caused by liraglutide may explain the reduction in MI, however this is offset by an increase in heart rate which may explain the lack of benefit in heart failure outcomes.